David Weir. Decadence: A Very Short Introduction. Oxford UP, 2018. - Patrick Moneyang (Studies in 20th & 21st Century Literature, 2019)
Review of David Weir. Decadence: A Very Short Introduction. Oxford UP, 2018. 132 pp.
Keywords: decadence; modernity